2021
DOI: 10.3390/jcm10081652
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Morbidity Following Vaginal Delivery versus Cesarean Delivery: Systematic Review and Meta-Analysis

Abstract: Objective: To compare pelvic floor disorders between vaginal delivery (VD) and cesarean delivery (CD). Methods: For this study, a PUBMED database search was used, utilizing a combination of relevant medical subjects’ headings (MeSH) terms, with the following keywords: “Pelvic floor disorders” or “Pelvic floor morbidity” and “Delivery”. Search limits were articles in English or Spanish, about women, published from December 2009 to December 2019. The STATA 16 package was used for meta-analysis and data heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…According to the evidence from a systematic review and a meta-analysis (2021), vaginal delivery can increase the risk of pelvic floor disorder [ 17 ]. This study introduced the increasing number of parities and the BMI as the risk factors in pelvic floor disorder [ 38 ]; however, another study reported that pelvic floor disorder had no significant correlations with the number of pregnancies and delivery [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the evidence from a systematic review and a meta-analysis (2021), vaginal delivery can increase the risk of pelvic floor disorder [ 17 ]. This study introduced the increasing number of parities and the BMI as the risk factors in pelvic floor disorder [ 38 ]; however, another study reported that pelvic floor disorder had no significant correlations with the number of pregnancies and delivery [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a review study has introduced genes as an effective factor in the emergence of pelvic floor disorder, especially pelvic organ prolapse distress [ 16 ]. The highest rate of pelvic floor disorders reported after vaginal delivery is related to urinary incontinence (28%) and pelvic organ prolapse (14%) [ 17 ]. Nevertheless, there is no evidence regarding the role of caesarean section in protecting pelvic floor muscles to prevent the potential occurrence of pelvic floor disorder [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anticipating and proactively managing FI and discussing future delivery in pregnant people with 1 or more prior obstetric anal sphincter injury (OASIS) is important because the risk of FI with prior OASIS and the risk of another OASIS in those with a history of OASIS are significantly increased (29)(30)(31). All women who have an episiotomy or a perineal tear at the time of delivery should undergo a rectal examination to evaluate for a rectal or anal sphincter injury.…”
Section: Management Of Fimentioning
confidence: 99%
“…Presently, PFDs are regarded as a hidden epidemic that affect approximately 21%-26% of women, with urinary incontinence (UI), having the highest incidence rates worldwide [2]. Pregnancy and delivery are independent risk factors for impaired pelvic floor function [3,4], with operative vaginal delivery (OVD) being closely associated with PFDs [5]. OVD refers to a key means of delivery in which forceps or vacuum extraction is used to apply direct traction on the fetal head during the second stage of labor to accelerate or achieve vagi-nal delivery [6].…”
Section: Introductionmentioning
confidence: 99%